Integration by emerging economy multinationals: perspectives from Chinese mergers and acquisitions - Muralidharan, Etayankara; Wei, William Xiaojun; Liu, Xiaoyu (My University, 2017)
The integration process of international mergers and acquisitions by emerging economy multinationals is fraught with challenges of liabilities of foreignness and country of origin. We use insights from institutional theory and draw on the experience of Chinese international mergers and acquisitions to explore these challenges faced by emerging economy multinationals during postmerger integration. We find that these challenges, which are primarily caused by informal institutional differences, can be overcome by developing organizational capabilities for integration and employing mechanisms for appropriate control and justice during the integration process. The study contributes to the ongoing discussions about the relevance of sociocultural influences in the successful integration of international mergers and acquisitions. Our framework proposes initiatives that managers from emerging economies can take to overcome postmerger integration challenges.
Keywords: international mergers; integration; emerging economies